Palliative radiotherapy combined with stent insertion to relieve dysphagia in advanced esophageal carcinoma patients: A systematic review and meta−analysis - Xu, Zhiyuan; Liu, Haonan; Li, Shengli; Han, Zhengxiang; Chen, Jingjing; Liu, Xiangting; Li, Qiang; Mu, Hong; Yuan, Jiaqi; Lu, Hailong; Jin, Peisheng; Yan, Xianliang (Frontiers in Oncology, 2022)
Introduction Esophageal cancer is one of the most aggressive malignancies with limited treatment options, thus resulting in high morbidity and mortality. For patients with advanced esophageal cancer, the median survival is 3–6 months, with the majority requiring intervention for dysphagia. Objective To compare the relief of dysphagia in patients with incurable esophageal cancer treated with stenting alone or a combination of stenting and palliative radiotherapy. Methods The protocol of this study was pre-registered on PROSPERO (CRD42022337481). We searched PubMed, Wan Fang, Cochrane Library, Embase, and Web of Science databases. The literature search, quality assessment, and data extraction were conducted by two reviewers independently. The primary endpoints included median overall survival and dysphagia scores. Bleeding events, stent migration, and pain events were secondary outcomes. The meta-analysis results (the primary and secondary outcomes) were pooled by means of a random-effect model or a fixed-effects model. Results Nine studies with a total of 851 patients were included in this meta-analysis, consisting of 412 patients in the stenting alone group and 439 patients in the palliative radiotherapy after esophageal cancer stenting (ROCS) group. The ROCS group could significantly improve dysphagia scores (SMD: −0.77; 95% CI: −1.02 to −0.51) and median overall survival (SMD: 1.70; 95% CI: 0.67–2.72). Moreover, there were no significant differences between the two groups in bleeding events, pain events, and stent migration. Conclusion Patients with dysphagia in advanced esophageal cancer may benefit further from ROCS in median overall survival and dysphagia scores. However, there was no significant advantage in improving bleeding events, pain events, and stent migration. Therefore, it is urgent to find a better therapy to improve adverse events in the future. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022337481.